![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
b) \(x^2-\left(x+4\right)\left(x+3\right)=24\)
\(\Leftrightarrow x^2-\left(x^2+7x+12\right)=24\)
\(\Leftrightarrow x^2-x^2-7x-12=24\)
\(\Leftrightarrow-7x-12=24\)
\(\Leftrightarrow-7x=36\)
\(\Leftrightarrow x=\frac{-36}{7}\)
a) \(x^2-x\left(2x+3\right)=2x-x^2+1\)
\(\Leftrightarrow x^2-2x^2-3x=2x-x^2+1\)
\(\Leftrightarrow5x+1=0\)
\(\Leftrightarrow x=\frac{-1}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^2 -2x = 24
=> x^2 - 2x - 24=0
=>x^2 -8x+6x - 24 = 0
=> ( x^2- 8x)+( 6x-24) = 0
=> x(x-8) + 6(x-8) = 0
=> (x+6)(x-8)=0
=>\(\orbr{\begin{cases}x=-6\\x=8\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x2 + 10x - 2x - 20 = 0
=> x(x + 10) - 2(x + 10) = 0
=> (x - 2)(x + 10) = 0
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x+10=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-10\end{cases}}\)
b) \(x^2-5x-24=0\)
\(\Rightarrow x^2-5x+\frac{25}{4}-\frac{121}{4}=0\)
\(\Rightarrow\left(x-\frac{5}{2}\right)^2=\frac{121}{4}\)
\(\Leftrightarrow\orbr{\begin{cases}\left(x-\frac{5}{2}\right)^2=\left(-\frac{11}{2}\right)^2\\\left(x-\frac{5}{2}\right)^2=\left(\frac{11}{2}\right)^2\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x-\frac{5}{2}=\left(-\frac{11}{2}\right)\\x-\frac{5}{2}=\frac{11}{2}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-\frac{6}{2}=3\\x=\frac{16}{2}=8\end{cases}}\)
c) x2 - 8x + 3x - 24 = 0
=> x(x - 8) + 3(x - 8) = 0
=> (x + 3)(x - 8) = 0
\(\Leftrightarrow\orbr{\begin{cases}x+3=0\\x-8=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x=8\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(25-x^2+\left(x+5\right)\left(2x+1\right)\)
\(=\left(5-x\right)\left(5+x\right)+\left(x+5\right)\left(2x+1\right)\)
\(=\left(x+5\right)\left(5-x+2x+1\right)\)
\(=\left(x+5\right)\left(x+4\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,x^2-2x=24\)
\(x^2-2x-24=0\)
\(x^2-2x+1-25=0\)
\(\left(x-1\right)^2=5^2=\left(-5\right)^2\)
\(x-1=5\) hoặc \(x-1=-5\)
\(\Rightarrow\hept{\begin{cases}x=6\\x=-4\end{cases}}\)
\(b,\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)
\(4x^2-4x+1+x^2+6x+9-5\left(x^2-49\right)=0\)
\(4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
\(2x+255=0\)
\(2x=-255\)
\(x=-\frac{255}{2}\)
a/ \(x^2-2x=24\)
<=> \(x^2-2x+1-1=24\)
<=> \(\left(x-1\right)^2=25\)
<=> \(\orbr{\begin{cases}x-1=25\\x-1=-25\end{cases}}\)<=> \(\orbr{\begin{cases}x=26\\x=-24\end{cases}}\)
b/ \(\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)
<=> \(4x^2-4x+1+x^2+6x+9-5\left(x^2-49\right)=0\)
<=> \(4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
<=> \(2x+255=0\)
<=> \(2x=-255\)
<=> \(x=-\frac{255}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^2 - 2x = 24
<=> x^2 - 2x - 24 = 0
<=> x^2 - 6x + 4x - 24 = 0
<=> ( x^2 - 6x ) + ( 4x - 24 ) = 0
<=> x ( x - 6 ) + 4 ( x - 6 ) = 0
<=> ( x - 6 ) ( x + 4 ) = 0
=> x - 6 =0 <=> x = 6
x + 4 = 0 x = - 4
ĐÂY NHÉ !!